(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Because of advances in science and technology, as well as the fact that the world is continuallygrowing, it appears that avoiding the presence of technology is becoming increasingly impossible thesedays. Every element of life has been impacted by rapid development and enormous improvements ininformation and telecommunication technologies. All of these technologies have been tried in a classroomenvironment. The mobility and accessibility of mobile devices has encouraged many academics to employthem in educational settings in this digital era. People’s lives are altering in a number of ways as aresult of this technology. In terms of social media, there has been a lot of advancement in digitaltechnology, but few people believe m-learning to be a necessary aspect of higher education. Thefindings demonstrate that using smart phones to study and repeat English vocabulary and phrases iseffective in enhancing university students’ foreign language proficiency. When creating such acurriculum, teachers must consider the requirements of the students, and teachers must give continualassistance. Only then will it be able to have a positive influence on student learning.